If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 = -3x + 5(-1x + 12) Reorder the terms: -4 = -3x + 5(12 + -1x) -4 = -3x + (12 * 5 + -1x * 5) -4 = -3x + (60 + -5x) Reorder the terms: -4 = 60 + -3x + -5x Combine like terms: -3x + -5x = -8x -4 = 60 + -8x Solving -4 = 60 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -4 + 8x = 60 + -8x + 8x Combine like terms: -8x + 8x = 0 -4 + 8x = 60 + 0 -4 + 8x = 60 Add '4' to each side of the equation. -4 + 4 + 8x = 60 + 4 Combine like terms: -4 + 4 = 0 0 + 8x = 60 + 4 8x = 60 + 4 Combine like terms: 60 + 4 = 64 8x = 64 Divide each side by '8'. x = 8 Simplifying x = 8
| Ln(x-4)+ln(x-1)=ln(x-8) | | lnx=-10 | | 2[x+5(6-x)+18]-10=50-10x | | 28=t+24 | | -8(-8+2p)=192 | | 3x-x+6x=17 | | 12c-4=-12c | | 12-5x=6(x+2) | | 3.4k=7.82 | | 2q-5=11 | | 225x^2-121y^2= | | 7+-3=18 | | 1-100x^2= | | (2c-1)=3c-2 | | 10+5(z-2)=-3z+3 | | 2x^3+3x^2-120=f(x) | | 3/4*3/4= | | -52=5x-4(-x-5) | | 2x^3+3x^2-120=0 | | 10-6x-3=1 | | 24(x+3)=0 | | 28-z=5 | | 2+14a=20a-5a | | z*z-(2+1i)z+(-1+7i)=0 | | -5x+2(-5x-5)=125 | | 2a+14a=20a-5a | | k/9=/18 | | 3-21=3x-9-2x | | -x+70=-86+5x | | 4(3x+2)-18= | | 6(z+2)-(6+4z)=z | | 3(x-3)=4(x+2) |